Longitudinal development of neuromuscular performance and multidirectional speed in youth badminton players: Evidence for parallel adaptation trajectories - Gepfert, M.; Golas, A.; Maszczyk, A.; Zajac, A.; Zwierzchowska, A. (Sensors, 2026)
This study examined long-term neuromuscular and multidirectional speed development in elite youth badminton players and evaluated whether developmental stage influences adaptation trajectories during systematic training. Thirty athletes were monitored over 16 months with repeated assessments at five time points and stratified into Younger (8-14 years) and Older (15-22 years) developmental groups. A comprehensive test battery assessed explosive strength, reactive strength, musculotendinous stiffness, and badminton-specific multidirectional speed. Data acquisition was performed using a multi-sensor approach, including force-platform-based jump analysis, accelerometry-based systems, and electronic timing gates, enabling the objective, high-resolution, and repeatable monitoring of neuromuscular performance. Significant time effects were observed across all sensor-derived performance variables (p < 0.001), indicating robust improvements in speed, power, and neuromuscular efficiency. Adaptation trajectories were predominantly linear, with no evidence of performance plateauing. Although older athletes maintained higher absolute performance levels, Time × Group interactions were largely absent, demonstrating parallel improvement rates across developmental stages rather than a catch-up effect in younger players. Linear mixed models confirmed equivalent improvement slopes despite baseline differences, and adjustment for body mass attenuated but did not eliminate age-group differences in jump performance. Exploratory analyses revealed substantial inter-individual variability, identifying responder phenotypes independent of age. These findings indicate that systematically progressed training supports sustained, linear neuromuscular adaptation across youth badminton development and highlight the importance of long-term, individualized monitoring over age-based expectations of accelerated responsiveness.